2019
DOI: 10.1177/1933719119828043
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Microarray Analysis of Plasma Proteins for the Prediction of Histologic Chorioamnionitis in Women With Preterm Premature Rupture of Membranes

Abstract: We aimed to identify maternal blood biomarkers predictive of histologic chorioamnionitis (HCA) in the plasma of women with preterm premature rupture of membranes (PPROM) and to determine whether the combination of these biomarkers with conventional clinical variables can improve the prediction of HCA. This retrospective cohort study included 82 consecutive women with PPROM (23-34 gestational weeks) who delivered within 96 hours of blood sampling. A membrane-based human antibody microarray was used to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…In the context of PPROM, IL-8 level in CVF is already consistently reported to have a significant correlation with MIAC [6,7,10,21], which is consistent with the current study. However, in the literature, CVF MMP- 9 has not yet been studied in regard to MIAC in PPROM, although it has been studied relatively extensively in AF or maternal blood [8,18,[21][22][23][24][25]. In the present study, we demonstrated that CVF MMP-9 is a useful non-invasive biomarker for MIAC in PPROM, and that the CVF level of MMP-9 was also significantly correlated with CVF IL-8 (r = 0.410).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In the context of PPROM, IL-8 level in CVF is already consistently reported to have a significant correlation with MIAC [6,7,10,21], which is consistent with the current study. However, in the literature, CVF MMP- 9 has not yet been studied in regard to MIAC in PPROM, although it has been studied relatively extensively in AF or maternal blood [8,18,[21][22][23][24][25]. In the present study, we demonstrated that CVF MMP-9 is a useful non-invasive biomarker for MIAC in PPROM, and that the CVF level of MMP-9 was also significantly correlated with CVF IL-8 (r = 0.410).…”
Section: Discussionsupporting
confidence: 54%
“…Elevated levels of TIMP-1 have been detected in the AF in the presence of MIAC [25,36]. In contrast to the results on a sample of AF, using histologic chorioamnionitis as the outcome variable, our previous study on maternal plasma has shown that TIMP-1 levels are not significantly changed in women with PPROM [18]. At present, however, no studies have examined the changes in TIMP-1 levels in CVF associated with MIAC, and we showed that TIMP-1 levels in CVF were significantly elevated in women with PPROM and MIAC.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…2, Additional file 5). In the 'Patient selection' domain, we judged 14 of the 23 studies to be at high risk of bias largely due to inappropriate exclusions such as excluding women based on duration after PPROM [35,38], not explicitly excluding women with clinical features of chorioamnionitis at the time of PPROM or at the time of admission [26,27,31,34,38,40], basing exclusions on availability or ability to perform other tests [31,40,45], excluding women due to missing data [34,35,50] and excluding women with common conditions and complications of pregnancy that often coexist with PPROM [32,36,39,40]. In the 'Index test' domain, all tests were considered to be 'blinded' because maternal blood was collected before delivery and assessed on automated assays.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Six studies specified that clinical features of chorioamnionitis were an indication for delivery [26,28,29,36,44,49]. According to the definitions of reference standard provided, 11 studies [26,28,31,35,36,[40][41][42][43][44]50] reported the index test against a reference standard of HCA and/ or funisitis, 10 [27, 29, 30, 32, 34, 39, 45, 46, 48, 49] reported HCA alone and 2 studies [33,38] reported funisitis alone. Characteristics of included studies are outlined in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%